2020
DOI: 10.3389/fendo.2020.00049
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Growth Hormone on the Endometrium in Assisted Reproductive Technology

Abstract: Growth hormone (GH) has been considered as an adjuvant treatment in human assisted reproductive technology (ART) for several years. Its action was largely attributed to an improvement of ovarian function and less emphasis was paid to its role in the uterus. However, there is increasing evidence that GH and its receptors are expressed and have actions in the endometrium and may play an important role in modifying endometrial receptivity. Thus, in this review, we firstly describe the existence of GH receptors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 58 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…The mechanisms underlying the effects of GH on endometrial thickness and uterine perfusion remain unclear. Animal models and in vitro cell cultures have been used to address this question, from basic science to the development and assessment of GH in clinical application ( 114 ). Targeted depletion of Ghr in mice leads to a detrimental impact on reproduction during early pregnancy because of fewer uterine implantation sites ( 115 ).…”
Section: Growth Hormone and Human Uterine Receptivitymentioning
confidence: 99%
“…The mechanisms underlying the effects of GH on endometrial thickness and uterine perfusion remain unclear. Animal models and in vitro cell cultures have been used to address this question, from basic science to the development and assessment of GH in clinical application ( 114 ). Targeted depletion of Ghr in mice leads to a detrimental impact on reproduction during early pregnancy because of fewer uterine implantation sites ( 115 ).…”
Section: Growth Hormone and Human Uterine Receptivitymentioning
confidence: 99%
“…A large majority of studies in the medical literature supplemented patients with GH, however, only during stimulation or, at best, starting about 2 weeks before stimulation start. Such supplementation, like androgen supplementation which supports follicle growth with identical timing [21], will not result in desired effects on granulosa cells of growing follicles (and, therefore, oocytes), though they may, at right concentrations, exert beneficial endometrial effects [35,36]. Second, the literature also varies greatly in daily dosages of GH that were administered.…”
Section: Limitations Summary and Conclusionmentioning
confidence: 99%
“…Studies in recent years have shown that growth hormone can improve ovarian responsiveness, promote endometrial growth, improve ovulation treatment in patients with low ovarian response, and increase pregnancy rates with cyclic ovulation. However, the use of growth hormone in the promotion of ovulation in patients with ROS warrants further investigation (89)(90)(91)(92). Mueller et al (63) reported a case of ROS in which follicle growth was not successfully induced with growth hormone.…”
Section: Growth Hormone Combined With Ovulation Inductionmentioning
confidence: 99%